Richard Turner‐Warwick: a father of reconstructive urology. Issue 3 (May 2017) - Hodgson, Dominic
Abstract : Richard Turner‐Warwick, or RTW as he is known, has had a significant influence on the advancement of urethral stricture surgery and of functional reconstructive urological surgery in the UK and worldwide. In this article, Dominic Hodgson, having met with and interviewed Richard, outlines some of the achievements of his long and very distinguished career.